RURAL SPRING GEOMETER MOTHS (LEPIDOPTERA, GEOMETROIDEA LEACH, 1815) IN KOSOVO AND METOHIA (SERBIA) - Živić, Nebojša V.; Jakšić, Predrag N. (Bulletin of Natural Sciences Research, 2020)
This paper shows the presence of the rural geometer moths in 15 localities of Kosovo and Metohia (Serbia). A review of existing data regarding the area of Kosovo and Metohia is given. Through research, the presence of 48 species was revealed. Between them, five species are reported as new for the fauna of Kosovo and Metohia: Plagodis pulveraria (Linnaeus, 1758), Scotopteryx luridata (Hufnagel, 1767), Catarhoe cuculata (Hufnagel, 1767), Anticlea badiata (Denis & Schiffermüller, 1775) and Anticlea derivata (Denis & Schiffermüller, 1775).